Punjab portraits - Tahir, M. Athar (Lahore : Sang-e-Meel Publications, 1992)
Essays and articles about different aspects, particularly cultural diversity of the modern as well as the old Punjab.
Includes bibliographical references.
Keywords: Punjab (India) -- Civilization